2006
DOI: 10.1111/j.1464-410x.2006.06135.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study comparing an antireflux system with a direct ureteric anastomosis in patients with orthotopic ileal neobladders

Abstract: Authors from Egypt conducted a randomized prospective study into the benefit of an anti‐reflux system in patients with orthotopic ileal neobladders. They found that anti‐reflux procedures were associated with a higher incidence of anastomotic structures. An editorial comment accompanies this paper, and together the two manuscripts make for interesting reading. OBJECTIVE To assess the benefit of an antireflux system in patients with orthotopic ileal neobladders, as there is controversy about whether reflux prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 34 publications
4
36
2
1
Order By: Relevance
“…Anastomotic strictures occurred in two cases and were successfully treated with minimal endoscopic procedures. Although the stricture rate in our study was higher than that reported by Fontana et al, it is still comparable with the results of other studies (18). We also failed to find any sign of obstruction of the uretero-ileal anastomosis on the antiperistaltic site of neobladder.…”
Section: Discussioncontrasting
confidence: 35%
“…Anastomotic strictures occurred in two cases and were successfully treated with minimal endoscopic procedures. Although the stricture rate in our study was higher than that reported by Fontana et al, it is still comparable with the results of other studies (18). We also failed to find any sign of obstruction of the uretero-ileal anastomosis on the antiperistaltic site of neobladder.…”
Section: Discussioncontrasting
confidence: 35%
“…However, several studies have demonstrated a higher rate of strictures with this technique than with refluxing anastomoses 5,27-29 , which is most likely attributed to the mechanical compression of the distal ureter. By contrast, several prospective randomized studies have shown no significant difference between the techniques 27,28,30 . Thus, the choice between nonrefluxing and refluxing anastomosis should be based on the surgeon's preference and experience.…”
Section: Perioperative Risk Factorsmentioning
confidence: 83%
“…Stenoses in the site of the ureter and the neobladder anastomosis most often occur in the first year after the operation and often result in asymptomatic ureterohydronephrosis due to its slow occurrence and course 15 . Stenosis in the site of anastomosis in direct methods of ureteral implantation is around 3.3% 16 . Our study reports a larger number of hydronephroses in the first six months due to reflux, however, after urinating, hydronephrosis completely spontaneously regressed in all patients except in two who were subjects to re-pouch-anastomosis.…”
Section: Resultsmentioning
confidence: 99%